2003
DOI: 10.1002/dc.10286
|View full text |Cite
|
Sign up to set email alerts
|

Atypical squamous cells of undetermined significance—rule out high‐grade squamous intraepithelial lesion: Cytopathologic characteristics and clinical correlates

Abstract: The significance and clinical management of atypical squamous cells of undetermined significance (ASCUS) on cervical cytologic smears has been an area of much controversy. This study compiled a list of criteria useful in identifying the subset of cases that would be categorized as atypical squamous cells of undetermined significance- rule out high-grade squamous intraepithelial lesion (ASC-H) in the new Bethesda System terminology, which eventuate in a diagnosis of cervical intraepithelial neoplasia (CIN). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
1
6

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 6 publications
6
42
1
6
Order By: Relevance
“…Furthermore, it is of some concern that 136 patients (18% of ASC-US women and 1.7% of ASC-H) had only cytologic sampling without histologic examination, a fact which may reflect a lack of knowledge about the appropriate follow-up of these equivocal Pap tests. However, modest decreases in rates of HSIL biopsy findings among ASC-H are also reported by other investigators (Alli and Ali, 2003;Bansal et al, 2012) suggesting that the diagnostic thresholds and disease Table 6. High-risk HPV positivity among ASC-US and ASC-H in different series DOI:http://dx.doi.org/10.7314/APJCP.2012.13.7…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, it is of some concern that 136 patients (18% of ASC-US women and 1.7% of ASC-H) had only cytologic sampling without histologic examination, a fact which may reflect a lack of knowledge about the appropriate follow-up of these equivocal Pap tests. However, modest decreases in rates of HSIL biopsy findings among ASC-H are also reported by other investigators (Alli and Ali, 2003;Bansal et al, 2012) suggesting that the diagnostic thresholds and disease Table 6. High-risk HPV positivity among ASC-US and ASC-H in different series DOI:http://dx.doi.org/10.7314/APJCP.2012.13.7…”
Section: Discussionmentioning
confidence: 59%
“…This gives rise to higher prevalence than the reality of clinical practice, reaching values from 26% to 68%. [13][14][15]17,18 Another likely reason was that we included cases in which the diagnostic conclusion was reached during the follow-up, which lowers the prevalence of the disease. According to Sherman et al, 23 the imperfect sensitivity of colposcopy for detecting small or focal pre-invasive lesions reinforces the need for strict follow-up among individuals with ASC-H cytology without lesions visible from colposcopy.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,11,12 Cross-sectional studies evaluating the prevalence of CIN II and III among individuals with ASC-H cytology have found values between 26 and 68%. [13][14][15][16][17][18][19] There is some evidence that this prevalence is lower after the menopause. 15,17,20,21 …”
Section: Introductionmentioning
confidence: 99%
“…In the recent study by Kingnate et al (2014), incidence of CIN 2-3/AIS and invasive lesion was 10.5% and 2.6%, respectively. In the literature, almost all studies evaluating histopathologic results of ASC-H smears were reported from North America where the incidence of cervical cancer appears to be relatively low (Alli and Ali, 2003;Louro et al, 2003;Selvaggi, 2003;Liman et al, 2005;Barreth et al, 2006;Saad et al, 2006;Srodon et al, 2006;McHale et al, 2007). The rate of underlying high-grade cervical lesion varied widely from 10% to 80%, in which less than 3.5% were invasive lesion (Alli and Ali, 2003;Louro et al, 2003;Selvaggi, 2003;Liman et al, 2005;Barreth et al, 2006;Saad et al, 2006;Srodon et al, 2006;McHale et al, 2007).…”
Section: Atypical Squamous Cells Cannot Exclude High-grade Squamous mentioning
confidence: 99%